ST-segment elevation myocardial infarction in the presence of metabolic-associated fatty liver disease - V. A. Tretyakova; O. V. Ermilov; P. K. Alferov; V. Yu. Chernyavskaya; D. I. Pisankina; A. Yu. Tretyakov (Российский кардиологический журнал)
Aim. To assess the characteristics of ST-segment elevation myocardial infarction (STEMI) in patients with metabolic syndrome (MS) in the presence and absence of metabolic-associated fatty liver disease (MAFLD).Material and methods. A total of 144 patients with STEMI and MS, admitted for primary coronary angiography and percutaneous intervention (PCI): 71 patients with MAFLD (group 1, age 62,9 (59,9;66,0) years, 17 women); 73 patients without MAFLD (control group, age 63,2 (59,1;66,8) years, 17 women). The examination program included transient hepatic elastography, determination of cardiac troponin I (cTnI) upon admission (cTnI-1) and after 24 hours (cTnI-24), mean platelet volume (MPV), transaminases, gamma-glutamyl transferase, concentration of cytokeratin-18 (CK-18) fragments.Results. Patients with STEMI in combination with MAFLD are characterized by the predominance of a high thrombotic load (TIMI thrombus grade 5, p=0,048), requiring two-stage PCI (p=0,018), an increase in the platelet count and MPV, a decrease in the resolution of ST elevation after primary PCI, a higher transaminase and liver dysfunction markers’ level. The main condition for these differences is steatohepatitis, which determines significant troponin elevation (p<0,01) and is a predictor of high thrombus load (p=0,016), increased MPV (p=0,044) and a factor of adverse events during 18 months after acute coronary syndrome (p=0,00035). The inclusion of the CK-18 criterion in the multivariate model makes it possible to improve the quality of the initial clinical model for predicting subsequent coronary events in the case of STEMI-MAFLD combination with an increase in the area under the ROC curve from 0,788 (95% confidence interval (CI), 0,69-0,89) to 0,648 (95% CI, 0,52-0,78) (DeLong test, p=0,044).Conclusion. MAFLD in patients with STEMI is combined with an increase in the severity of coronary thrombosis and difficulties in primary PCI, the main condition of which, as well as adverse events after acute coronary syndrome, is steatohepatitis.